A Wide Variation in Diagnostic and Therapeutic Strategies in Chronic Pancreatitis: A Dutch National Survey - van Esch, Aura AJ; Ahmed Ali, Usama; van Goor, Harry; Bruno, Marco J; Drenth, Joost PH (JOP. Journal of the Pancreas, 2012)
Context Optimal diagnostic and treatment modalities in chronic pancreatitis are controversial due to lack of evidence. Objective To evaluate current clinical practice, we conducted a survey with the primary objective to evaluate decisions regarding the diagnosis, management and screening in chronic pancreatitis. Design We developed a vignette survey. Setting We surveyed Dutch gastroenterologists, internists, gastrointestinal surgeons and an international expert panel. Results A total of 110 questionnaires (31% gastroenterologists, 39% internists and 20% gastrointestinal surgeons) were returned out of the 1,324 sent (response 8.3%). There was a wide variation in strategies regarding diagnosis, treatment and screening in chronic pancreatitis. As a diagnostic test, serum amylase is used frequently by internists, while gastroenterologists and experts often use fecal elastase. Most respondents preferred CT-scanning for diagnosis, while experts preferred transabdominal ultrasonography as an initial test. Respondents frequently use pancreatic enzymes for treatment of pain in chronic pancreatitis. The majority advised to perform an intervention (endoscopic or surgical) in case of morphological changes of the pancreatic duct. Conclusions The results of our survey identify important differences between physicians in diagnosis and management of chronic pancreatitis. This is often due to lack of evidence and consensus in literature. Certain wide-spread practices are in contrast with available evidence, and should be addressed by improved education and adherence to guidelines. Image: Different laboratory tests in the diagnostic strategy of chronic pancreatitis.